Pharmacokinetic Evaluation of [18f]Pr04.Mz for Pet/Ct Imaging and Quantification of Dopamine Transporters in the Human Brain - Chana-Cuevas, P (Springer, 2020)
Purpose: Dopamine transporters (DAT) modulate pre-synaptic dopamine and physiological functions such as movement and reward. DAT also mirrors disease state in neurological disorders, rendering it an essential diagnostic target. [18F]PR04.MZ is a new PET imaging agent for DAT with an improved affinity and selectivity profile, for which we here describe the complete pharmacokinetic evaluation in healthy controls. Methods: Thirty-two healthy subjects underwent T1-weighted MRI and dynamic PET scans for 180 min with arterial blood sampling (n = 5) or 90 min without blood sampling (n = 25) after injection of 197.6 ± 12.2 MBq [18F]PR04.MZ. Blood and plasma metabolite analysis were performed. MRI-based normalization of brain images, delineation of VOIs, and kinetic modeling was conducted to determine distribution volumes (Vt) and binding potentials (BPnd). The impact of scan duration was evaluated and repeated PET scans were performed to assess test-retest variability (n = 5). A static imaging protocol has been validated for clinical applications. Results: [18F]PR04.MZ showed rapid metabolization in circulation, very high uptake in striatum and midbrain, and very low non-specific binding. The two-tissue compartment model 2TCM provided best fits for measured time-activity-curves and calculated Vts in putamen, caudate, substantia nigra pars compacta (SNpc), and cerebellar cortex were 11.83, 9.73, 2.12, and 0.57, respectively. All non-invasive models correlated well with BPnd values derived from 2TCM but underestimated DAT availability by about 28–33%. Of those, simplified reference tissue model (SRTM) provided the best fits, lowest Akaike Information Criteria values, and BPnd values of 14.82, 11.95, and 2.63 in putamen, caudate, and SNpc, respectively. BPnd estimates for striatal regions and SNpc were stable between 90 and 130 min post-injection. Test-retest results were excellent, showing low variability in all and excellent reliability in most relevant regions. Static imaging from 60 to 90-min post-injection is a viable alternative for quantification. Conclusions: [18F]PR04.MZ is a PET tracer with very high affinity, selectivity, and specific uptake in striatum and midbrain. 2TCM and SRTM provide good fits, high and stable Vts or BPnds, and good test-retest reliability for precise quantification of DAT in human subjects. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.